Diagenetic stabilization of the Upper Permian Dalan Formation, Persian Gulf Basin. (March 2020) - Fallah-Bagtash, Roghayeh; Jafarian, Arman; Husinec, Antun; Adabi, Mohammad Hossein
Graphical abstract: Highlights: Upper Dalan carbonates underwent diagenesis in 6 early-to-late diagenetic settings. Diagenetic alteration occurred in a closed system. Four texturally and isotopically different dolomite types were identified. Dolomitization occurred via 2 reflux episodes followed by deep-burial stabilization. Abstract: The Upper Permian Dalan Formation is a supergiant gas reservoir in the Persian Gulf Basin. Reservoir quality is controlled by the original facies type, dolomitization, and anhydrite cementation. This study focuses on the texture (petrographic analysis), bulk stable-isotope values, and trace element composition in order to identify the original mineralogy of carbonate grains and cements, and to assess the synsedimentary and diagenetic processes, including the timing and setting of dolomitization. The limestone data suggest that the initial precipitation of isopachous acicular to fibrous aragonite cements in the marine phreatic environment was followed by dissolution of aragonite grains and cements in the meteoric phreatic zone, and neomorphism and low-Mg calcite cementation (blocky and drusy crystals, syntaxial overgrowths) in the active freshwater phreatic zone. The relatively pristine δ 18 O and δ 13 C values, low Mn and relatively high Sr and Na contents indicate that this meteoric diagenesis was relatively limited. The remaining porous space was cemented by blocky calcite later during burial. Four types of dolomites are identified within a complex mixture of texturally and isotopically different dolomites: dolomicrite, dolomicrosparite, dolosparite, and saddle dolomite. Dolomicrite formed syndepositionally from the evaporated Permian seawater or by reflux of dense evaporated brines during shallow burial. The second major episode of dolomitization (dolomicrosparite and dolosparite) was driven by reflux of warmer and more saline fluids at greater depth, which affected both previously non-dolomitized and dolomitized sediments. The final diagenetic stabilization during deep burial is associated with extensive pressure solution, fracturing, vein-filling of calcite and dolomite cements, and crystallization of saddle dolomite.